(untitled) (Annals of Medical Research, 2025)
Aim: Sustainability consciousness (SC) refers to the awareness and lived experience of sustainability phenomena, which includes personal insights and viewpoints. The objective of this study is to assess the correlation between SC and physical activity among young, healthy volunteers. Materials and Methods: We assessed sustainability consciousness (SC) using the Sustainability Consciousness Questionnaire (SCQ) and physical activity levels with the International Physical Activity Short Form (IPAQ-sf). Results: We included 235 participants in the study, with ages ranging from 18 to 33 years and an average BMI of 23.01. The study found no statistically significant association between overall physical activity levels (IPAQ-SF) and overall sustainability consciousness (SCQ) (p > .05). Furthermore, none of the IPAQ-SF sub-parameters showed a significant correlation with the SCQ’s total scores for knowledge (r=-.014, p=.835), attitude (r=-.007, p=.912), or behavior (r=.070, p=.287). When examining the SCQ sub-parameters, we found no significant association between knowledge (economic) and attitude (environment) (r=-.040, p=.539), or between knowledge (economic) and behavior (social) (r=-.047, p=.472). However, all other SCQ sub-parameters showed significant intercorrelations (p<.001). Specifically, knowledge (social) and behavior (social) sub-parameters were not significantly related (r=.026, p=.689), but all other pairings within the SCQ sub-parameters were significantly correlated (p<.001). Conclusion: This study found no association between sustainability consciousness (SC) and physical activity in healthy young individuals. However, we did observe significant interrelationships among the knowledge, attitude, and behavior sub-parameters of the Sustainability Consciousness Questionnaire (SCQ), across economic, social, and environmental dimensions.